Translation of statechart agents into a BDI framework for MAS engineering. (May 2015) - Fortino, Giancarlo; Rango, Francesco; Russo, Wilma; Santoro, Corrado
Abstract: In the agent-oriented computing area, different programming paradigms have been to date proposed to design and implement multi-agent systems (MAS). Among them, the Belief-Desire-Intention (BDI) and Statecharts-based models have emerged as they effectively support the definition of rational and protocol-oriented agent behaviors, respectively. In this paper, we investigate the translation between such models by using two available agent modeling languages: PROFETA, which is based on the BDI agent model, and the agent-oriented Distilled StateCharts (DSC) formalism, which allows modeling agent behaviors based on Statecharts-like state machines. In particular, we propose a mapping from DSC to PROFETA that can enable visual programming of PROFETA programs to facilitate the development of PROFETA-based autonomous systems. A case-study is also developed to exemplify the proposed engineering approach.